2014
DOI: 10.1111/febs.12804
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional diversity of metalloproteinases encoded by the Bacteroides fragilis pathogenicity island

Abstract: Summary Bacteroides fragilis causes the majority of anaerobic infections in humans. The presence of a pathogenicity island in the genome discriminates pathogenic and commensal B. fragilis strains. The island encodes metalloproteinase II (MPII), a potential virulence protein, and one of three homologous fragilysin isozymes (FRA; also termed B. fragilis toxin or BFT). Here, we report biochemical data on the structural-functional characteristics of the B. fragilis pathogenicity island proteases by reporting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…This technology includes cleavage of a large number of peptide-cDNA fusions designed in silico and then synthesized in vitro . The technology has been tested and validated by determining cleavage preferences of several viral, bacterial and human proteinases (Kozlov, et al, 2012; Shiryaev, et al, 2014; Shiryaev, et al, 2013; Shiryaev, et al, 2013; Shiryaev, et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology includes cleavage of a large number of peptide-cDNA fusions designed in silico and then synthesized in vitro . The technology has been tested and validated by determining cleavage preferences of several viral, bacterial and human proteinases (Kozlov, et al, 2012; Shiryaev, et al, 2014; Shiryaev, et al, 2013; Shiryaev, et al, 2013; Shiryaev, et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…To determine cleavage preferences of MMPs, we employed a high throughput multiplexed peptide-centric profiling technology that we developed (Kozlov, et al, 2012; Shiryaev, et al, 2014; Shiryaev, et al, 2013; Shiryaev, et al, 2013). In this study, we treated a pool containing 18,583 peptide-cDNA fusions with 18 MMPs (one proteinase per reaction).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we demonstrated that the supplementation of infant formula with bifidobacteria inversely correlated with B. fragilis colonization throughout the first year of life, showing similarities to the breastfed gut ecosystem, while placebo-fed infants were more often colonized by this species. B. fragilis contributes to the development and maturation of the infant immune system (47), but it also encodes virulent metalloproteases and other pathogenic features, making it one of the most popular anaerobic pathogens of the human gut (48). Moreover, one recent study showed that Bacteroides species are less abundant in Russian infants but are dominant in Finnish and Estonian infant cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…FRAs exist in three homologous isoforms (FRA1, 2 and 3) with sequence identities of over 95%, while the sequence identity between FRAs and MPII is ∼25%. Both FRA and MPII are secretory metalloproteinases with a zinc-binding HEXXHXXGXXH motif and a characteristic Met-turn [9] [11] in their catalytic domain that has a classic “metzincin” fold typical of eukaryotic matrix metalloproteases. The crystal structure of FRA3 was reported earlier [10] .…”
Section: Introductionmentioning
confidence: 99%